Lariat intronic RNAs in the cytoplasm of Xenopus tropicalis oocytes - Talhouarne, Gaëlle J.S. (Cold Spring Harbor Laboratory Press, 2014)
We previously demonstrated that the oocyte nucleus (germinal vesicle or GV) of Xenopus tropicalis contains a population of stable RNA molecules derived from the introns of most expressed genes. Here we show that similar stable intronic sequence (sis) RNAs occur in the oocyte cytoplasm. About 9000 cytoplasmic sisRNAs have been identified, all of which are resistant to the exonuclease RNase R. About half have been confirmed as lariat molecules and the rest are presumed to be lariats, whereas nuclear sisRNAs are a mixture of lariat and linear molecules. Cytoplasmic sisRNAs are more abundant on a molar basis than nuclear sisRNAs and are derived from short introns, mostly under 1 kb in length. Both nuclear and cytoplasmic sisRNAs are transmitted intact to the egg at GV breakdown and persist until at least the blastula stage of embryogenesis, when zygotic transcription begins. We compared cytoplasmic sisRNAs derived from orthologous genes of X. tropicalis and X. laevis, and found that the specific introns from which sisRNAs are derived are not conserved. The existence of sisRNAs in the cytoplasm of the oocyte, their transmission to the fertilized egg, and their persistence during early embryogenesis suggest that they might play a regulatory role in mRNA translation.